Recent Progress on Photothermal Heterogeneous Catalysts for CO2 Conversion Reactions. Issue 2 (14th November 2021) - Liu, Huimin; Gao, Xiaoxu; Shi, Dongchen; He, Dehua; Meng, Qingrun; Qi, Ping; Zhang, Qijian
Abstract : Converting the greenhouse gas carbon dioxide into important chemical fuels is promising to alleviate the global warming problem. Photocatalytic CO2 reduction is beneficial for energy storage and environmental protection; however, it suffers from low efficiency. Recently, photothermal catalysis, which merits the advantages of both photocatalysis and traditional thermally driven catalysis, has been extensively studied and proven promising. Herein, the scope of catalyst type within heterogeneous catalysts is discussed, the latest progress of photothermal heterogeneous catalysts designed for CO2 conversion reactions is described, including the reduction of CO2 by H2 O, CO2 hydrogenation to CO, CH4, CH3 OH, or C2+, CO2 reforming of CH4 (CRM), CO2 cycloaddition reaction, etc. the preparation principles of photothermal catalysts are summarized, the challenges on the design and development of highly efficient photothermal catalysts are pointed out, and the future research directions are prospected. Abstract : Herein, the latest progress on photothermal heterogeneous catalysts for CO2 conversion reactions is summarized. The design principles on photothermal catalysts are generalized, the remaining challenges and tasks are pointed out, and the future of this research area is prospected, with the aim to give the readers a clear picture of this prosperous field.